Perovskite precursor solution, perovskite solar cell and preparation method thereof

By adding organic salts of trifluoromethyl acid to the perovskite precursor solution, the problems of poor quality of perovskite solar cell thin films, lead iodide precipitation and crystallization inhomogeneity are solved, and the effect of improving photovoltaic performance and stability is achieved.

CN119907612APending Publication Date: 2025-04-29UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202510072619.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing perovskite solar cells have defects and shortcomings, including poor film quality, lead iodide precipitation after annealing, insufficient photovoltaic performance and stability, and the problem of crystallization of large-area thin films.

Method used

The organic salt of trifluoromethyl acid is introduced as an additive in the perovskite precursor solution to improve the film quality, reduce the precipitation of lead iodide, improve photovoltaic performance and stability, and improve crystallization inhomogeneity during vacuum quenching of large-area films.

Benefits of technology

By introducing organic salts of trifluoromethyl acids, the photovoltaic performance and operating stability of perovskite solar cells are significantly improved, the precipitation of lead iodide is reduced, and the crystallization uniformity of the film is improved. It is suitable for the preparation of small and large-area batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907612A_ABST
    Figure CN119907612A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite precursor solution, a perovskite solar cell and a preparation method of the perovskite solar cell. The perovskite precursor solution provided by the invention contains a perovskite precursor solute, a perovskite precursor solvent and an additive, the perovskite precursor solute contains lead halide, and further contains at least one of tin halide, formamidine halide, methylamine halide, cesium halide, dimethylamine halide and guanidine halide; the perovskite precursor solvent contains at least one of N, N-dimethyl formamide, dimethyl sulfoxide, N-methyl pyrrolidone, 2-methoxyethanol, valerolactone and acetonitrile, and the perovskite precursor solvent contains at least one of N, N-dimethyl formamide, dimethyl sulfoxide, N-methyl pyrrolidone, 2-methoxyethanol, valerolactone and acetonitrile; the additive contains an organic salt of trifluoromethyl acid. The opening voltage loss is reduced, the filling factor and the photoelectric conversion efficiency of the battery are improved, the precipitation of lead iodide is reduced in the crystallization annealing process, the volatilization of organic cations is inhibited, the non-uniform crystallization is improved, and the stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and more specifically, relates to a perovskite precursor solution, a perovskite solar cell and a preparation method thereof. Background Art

[0002] Organic-inorganic hybrid metal halide perovskite materials have the characteristics of adjustable band gap, high absorption coefficient, low processing cost, and relatively simple preparation process. The certified photoelectric conversion efficiency of solar cells based on this type of material has exceeded 26.1%, and the certified efficiency of perovskite / silicon two-terminal stacked solar cells has reached 34.6%. Both have great market application potential in the field of photovoltaic power generation. In the most common solution preparation process, the wet film formed by the perovskite precursor solution generally needs to be removed by anti-solvent, vacuum quenching and nitrogen quenching to remove excess solvent, so that the perovskite solute is quickly saturated and nucleated and crystallized. Therefore, the crystallization process greatly affects the final quality of the perovskite film. Passivation engineering and additive engineering are often used to modify perovskite cells. With the deepening of research, the preparation of efficient and stable perovskite solar cells has become a current research hotspot.

[0003] Defects generated during the preparation of perovskite films will promote the degradation of perovskite materials that are sensitive to water and oxygen and the migration of halogen ions during battery operation, thereby reducing battery conversion efficiency and operational stability and accelerating battery aging. On the other hand, wide-bandgap perovskites (around 1.65 eV) facing the perovskite-silicon stack usually contain more cesium and bromine components, which are prone to form phase segregation of cesium-rich or bromine-rich perovskites during the nucleation process, reducing the uniformity of the film. Therefore, controlling the quality of perovskite films is crucial to improving the photovoltaic properties of perovskite solar cells and promoting their commercialization. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of existing perovskite solar cells and provide a perovskite precursor solution, a perovskite solar cell and a preparation method thereof.

[0005] The first object of the present invention is to provide a perovskite precursor solution.

[0006] The second object of the present invention is to provide a method for preparing the perovskite precursor solution.

[0007] The third object of the present invention is to provide the use of the perovskite precursor solution in the preparation of perovskite solar cells, perovskite light-emitting diodes, perovskite lasers, perovskite photodetectors and / or optical chips.

[0008] The fourth object of the present invention is to provide a method for preparing a perovskite solar cell.

[0009] The fifth object of the present invention is to provide a perovskite solar cell prepared by the preparation method.

[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0011] The present invention provides a perovskite precursor solution, wherein the perovskite precursor solution contains a perovskite precursor solute, a perovskite precursor solvent and an additive;

[0012] The perovskite precursor solute contains lead halide and at least one of tin halide, formamidine halide, methylamine halide, cesium halide, dimethylamine halide and guanidine halide;

[0013] The perovskite precursor solvent contains at least one of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol, valerolactone and acetonitrile;

[0014] The additive contains an organic salt of trifluoromethyl acid.

[0015] The present invention introduces an organic salt of trifluoromethyl acid as an additive into a perovskite precursor solution to improve the quality of the film and reduce the lead iodide precipitation of the film after annealing. The photovoltaic performance and operating stability of the device are improved. In addition, the organic salt of trifluoromethyl acid improves the crystallization non-uniformity that may be caused by the vacuum quenching process of a large-area film.

[0016] Preferably, the organic salt of the trifluoromethyl acid contains at least one of methylamine ion, ethylamine ion, dimethylamine ion and ethylenediamine ion, and the trifluoromethyl acid includes one of trifluoroacetic acid, trifluoropropionic acid, trifluorobutyric acid and trifluoromethylbenzoic acid.

[0017] Further, in the perovskite precursor solute, the lead halide includes at least one of lead iodide, lead bromide and lead chloride;

[0018] The tin halide includes at least one of tin iodide, tin bromide, tin chloride and tin fluoride;

[0019] The halogenated formamidine comprises at least one of formamidine iodide, formamidine bromide and formamidine chloride;

[0020] The methylamine halide comprises at least one of methylamine iodide, methylamine bromide and methylamine chloride;

[0021] The cesium halide includes at least one of cesium iodide, cesium bromide and cesium chloride;

[0022] The dimethylamine halide includes at least one of dimethylamine iodide, dimethylamine bromide and dimethylamine chloride;

[0023] The guanidine halogenide includes at least one of guanidine iodide, guanidine bromide and guanidine chloride.

[0024] In a specific embodiment of the present invention, the perovskite precursor solute contains methylamine chloride, cesium iodide, formamidine iodide, lead bromide and lead iodide. The perovskite precursor solvent contains N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide. The additive contains ethylamine trifluoroacetic acid or dimethylamine trifluoroacetic acid.

[0025] Furthermore, the band gap of the perovskite is 1.23 to 1.78 eV.

[0026] Furthermore, the total concentration of the lead halide is 0.8-1.8 mol / L. Preferably, the band gap of the perovskite is 1.66 eV, and the total concentration of the lead halide is 1.4 mol / L; the band gap of the perovskite is 1.55 eV, and the total concentration of the lead halide is 1.63 mol / L.

[0027] Furthermore, the content of methylammonium chloride is 5 to 30 mol% relative to the molar ratio of lead; the content of cesium iodide is 3 to 26 mol% relative to the molar ratio of lead; the content of formamidine iodide is 74 to 97 mol% relative to the molar ratio of lead; the content of lead bromide is 0 to 22.5 mol% relative to the molar ratio of lead; and the content of lead iodide is 77.5 to 100 mol% relative to the molar ratio of lead.

[0028] In a specific embodiment of the present invention, the perovskite component with a band gap of 1.66 eV has a content of 0.084 mol / L of methylammonium chloride, which is 6 mol% in molar ratio to lead; a content of 0.364 mol / L of cesium iodide, which is 26 mol% in molar ratio to lead; a content of 1.036 mol / L of formamidine iodide, which is 74 mol% in molar ratio to lead; a content of 0.315 mol / L of lead bromide, which is 22.5 mol% in molar ratio to lead; and a content of 1.085 mol / L of lead iodide, which is 77.5 mol% in molar ratio to lead.

[0029] In a specific embodiment of the present invention, the perovskite component with a band gap of 1.55 eV has a content of 0.48 mol / L of methylammonium chloride, which is 30 mol% in molar ratio to lead; a content of 0.05 mol / L of cesium iodide, which is 3 mol% in molar ratio to lead; a content of 1.5 mol / L of formamidine iodide, which is 90 mol% in molar ratio to lead; a content of 0.03 mol / L of lead bromide, which is 1.8 mol% in molar ratio to lead; and a content of 1.6 mol / L of lead iodide, which is 98.2 mol% in molar ratio to lead.

[0030] Furthermore, the volume ratio of the N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide is 4-50:0-5:1.

[0031] In a specific embodiment of the present invention, the gap of the perovskite is 1.66 eV, and the volume ratio of the N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide is 44.1:4.9:1; the gap of the perovskite is 1.55 eV, the volume ratio of the N,N-dimethylformamide and dimethyl sulfoxide is 4:1, and the perovskite precursor solvent does not contain N-methylpyrrolidone.

[0032] Furthermore, the molar ratio of the organic salt of trifluoromethyl acid to lead in the perovskite precursor solute is 0.01 to 5 mol%.

[0033] As a preferred embodiment of the present invention, the molar ratio of the organic salt of trifluoromethyl acid to lead in the perovskite precursor solute is 0.05 to 2 mol%.

[0034] Preferably, the band gap of the perovskite is 1.66 eV, the content of the organic salt of trifluoromethyl acid in the perovskite precursor solute is 0.028 mol / L, and the molar ratio relative to lead is 2 mol%; the band gap of the perovskite is 1.55 eV, the content of the organic salt of trifluoromethyl acid in the perovskite precursor solute is 0.004 mol / L, and the molar ratio relative to lead is 0.25 mol%.

[0035] The present invention also provides a method for preparing the perovskite precursor solution, and the perovskite precursor solute, the perovskite precursor solvent and the additive are uniformly mixed to obtain the perovskite precursor solution.

[0036] As a preferred embodiment of the present invention, the uniform mixing time is 6 to 12 hours.

[0037] In a specific embodiment of the present invention, the perovskite precursor solute, the perovskite precursor solvent and the additive are mixed uniformly for 12 hours.

[0038] The present invention also provides the use of the perovskite precursor solution in the preparation of perovskite solar cells, perovskite light-emitting diodes, perovskite lasers, perovskite photodetectors and / or optical chips.

[0039] The present invention also claims a method for preparing a perovskite solar cell, comprising the following steps:

[0040] S1: Preparation of hole extraction layer on conductive glass;

[0041] S2: preparing a porous insulating contact layer on the hole extraction layer in step S1;

[0042] S3: depositing a perovskite layer on the porous insulating contact layer obtained in step S2 using the perovskite precursor solution according to any one of claims 1 to 3;

[0043] S4: preparing an electron transport layer on the perovskite layer in step S3;

[0044] S5: preparing a hole blocking layer on the electron transport layer in step S4;

[0045] S6: preparing a back electrode layer on the hole blocking layer in step S5.

[0046] Furthermore, in step S1, the conductive glass includes conductive glass doped with tin oxide (FTO) and / or doped with indium tin oxide (ITO).

[0047] Furthermore, in step S1, the hole extraction layer material is a p-type semiconductor material.

[0048] Further, in step S1, the hole extraction layer material includes one or more of nickel oxide (NiO), copper phthalocyanine (CuPc), 4-butyl-N,N-diphenylaniline homopolymer (Poly-TPD), [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) and its derivatives and poly [bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA); the derivatives of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) include [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) and / or [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz).

[0049] Furthermore, in step S1, the method for preparing the hole extraction layer includes at least one of spin coating, thermal evaporation, blade coating and slit coating.

[0050] Furthermore, in step S1, the thickness of the hole extraction layer is 0.5-2 nm, preferably 1 nm.

[0051] Furthermore, in step S2, the porous insulating contact layer material includes at least one of lithium fluoride (LiF), aluminum oxide (Al2O3) and silicon oxide (SiO2).

[0052] In a specific implementation manner of the present invention, experiments were conducted using aluminum oxide (Al2O3) as an example.

[0053] Furthermore, in step S2, the method for preparing the porous insulating contact layer includes at least one of a spin coating method, a blade coating method and a slit coating method.

[0054] Further, in step S3, the perovskite layer is deposited in nitrogen and / or air.

[0055] Further, in step S3, the method of depositing the perovskite layer includes at least one of spin coating, doctor blading, slit coating, inkjet printing and screen printing.

[0056] In a specific embodiment of the present invention, the method of depositing the perovskite layer includes spin coating and / or doctor blade coating.

[0057] In a specific embodiment of the present invention, the perovskite layer is prepared by a spin coating-anti-solvent method: the perovskite precursor solution is spin coated on the porous insulating contact layer of step S2 at a rotation speed of 4000-5000 r / min for 30-40s, and annealed on a hot stage at 100-120°C for 15-30min to complete the annealing crystallization of the perovskite layer.

[0058] Preferably, the perovskite precursor solution is spin-coated on the porous insulating contact layer in step S2 at a rotation speed of 5000 r / min for 30 seconds, and annealed on a hot plate at 120° C. for 20 minutes to complete the annealing crystallization of the perovskite layer.

[0059] In a specific embodiment of the present invention, the perovskite layer is prepared by a blade coating-vacuum quenching method:

[0060] S31: The gap height between the scraper and the porous insulating contact layer is 100-150 μm, the perovskite precursor solution is squeezed into the gap, and then the scraper spreads the perovskite precursor solution on the porous insulating contact layer into a uniform wet film at a speed of 1-1.8 mm / s to obtain a porous insulating contact layer substrate with a spread wet film;

[0061] S32: Rapidly transfer the porous insulating contact layer substrate on which the wet film is spread in step S31 to a sealable chamber for pre-crystallization, evacuate the chamber to maintain the chamber pressure at 0.2-2 Pa, restore the chamber pressure after 1-5 minutes, and place it on a hot plate at 100-120°C for annealing for 20-30 minutes to complete the annealing crystallization of the perovskite layer.

[0062] The purpose of vacuuming is to evaporate the excess solvent under low pressure, so that the perovskite solute can be quickly saturated, nucleate and crystallize, and complete the transformation of the perovskite film from a wet film to an intermediate phase film.

[0063] Preferably, in step S32, the chamber is evacuated to maintain the chamber pressure at 2 Pa, and the chamber pressure is restored after 3 minutes, and the chamber is placed on a hot plate at 120° C. for annealing for 20 minutes to complete the annealing crystallization of the perovskite layer.

[0064] Furthermore, in step S4, an electron transport layer is prepared using an n-type semiconductor material.

[0065] Furthermore, in step S4, the n-type semiconductor material includes fullerene (C 60 ), fullerene (C 60 ) derivative (PCBM), tin oxide (SnO2) or at least one of the above.

[0066] In a specific embodiment of the present invention, fullerene (C 60 ) as an example for the experiment.

[0067] Furthermore, in step S4, the method for preparing the electron transport layer includes a thermal evaporation method.

[0068] Furthermore, in step S4, the thickness of the electron transport layer is 15 to 30 nm, preferably 20 nm.

[0069] Furthermore, in step S5, the hole blocking layer material includes bathocuproin (BCP), titanium tetrachloride (TiCl4) and tin oxide (SnO x ) at least one of.

[0070] In the specific implementation manner of the present invention, bathocuproine (BCP) is used as an example for experiment.

[0071] Furthermore, in step S5, the method for preparing the hole blocking layer includes a thermal evaporation method.

[0072] Furthermore, in step S5, the thickness of the hole blocking layer is 3-8 nm, preferably 5 nm.

[0073] Furthermore, in step S6, the method for preparing the back electrode layer includes a thermal evaporation method.

[0074] Furthermore, in step S6, the back electrode layer is Ag with a thickness of 80-200 nm, preferably 100 nm.

[0075] The present invention also provides a perovskite solar cell prepared by the preparation method.

[0076] The present invention has the following beneficial effects:

[0077] The present invention provides a perovskite precursor solution and method for improving the quality of perovskite solar cells. A small amount of trifluoromethyl acid organic salt is added to the perovskite precursor solution for modification. The ammonium salt ions reduce the opening voltage loss of the wide bandgap perovskite, thereby improving the filling factor and photoelectric conversion efficiency of the battery. The trifluoromethyl group coordinates with the unsaturated lead ions, reduces the precipitation of lead iodide during the crystallization annealing process, and inhibits the volatilization of organic cations. The migration of halogen anions to the electronic layer interface and the metal electrode is effectively inhibited, and the maximum power point tracking stability of the battery is significantly improved. This method is not only applicable to the conventional spin coating-antisolvent method of small-area batteries, but is also effective for the enlarged scraping-vacuum quenching preparation method, and can improve the uneven crystallization that may be caused by the vacuum quenching process of large-area thin films. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 SEM image of the cross section of a perovskite solar cell and the corresponding device structure.

[0079] Figure 2 Time-of-flight secondary ion mass spectrum of perovskite solar cells modified with organic salts of trifluoromethyl acid.

[0080] Figure 3 The current density-voltage curves corresponding to Example 2 (optimal additive content) and Comparative Example 1 listed in Table 1 are shown.

[0081] Figure 4 1 and 2 are XRD spectra of the perovskite films corresponding to Example 2 and Comparative Example 1, respectively.

[0082] Figure 5 The XPS spectra of the perovskite films corresponding to Example 1, Example 2 and Comparative Example 1, respectively.

[0083] Figure 6 This is the XRD spectrum of the perovskite intermediate phase film under vacuum quenching for different lengths of time in control example 3.

[0084] Figure 7 XRD patterns of the perovskite intermediate phase film under vacuum quenching for different time periods in Example 6.

[0085] Figure 8 Graphs showing the ELQE of the perovskite solar cells corresponding to Example 2 and Comparative Example 1 as a function of the injected current density.

[0086] Fig. 9 The stability of the perovskite solar cells corresponding to Example 2 and Comparative Example 1 under a standard solar simulated light source under a maximum power point tracking test.

[0087] Fig.10 The local XRD patterns of the perovskite intermediate phase film of comparative example 6 after vacuum quenching with dimethylamino formic acid for different time periods.

[0088] Fig.11 The local XRD patterns of the perovskite intermediate phase film under vacuum quenching for different time periods in comparative example 6.

[0089] Fig.12 The local XRD patterns of the perovskite intermediate phase film under vacuum quenching for different time periods in Example 6. DETAILED DESCRIPTION

[0090] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0091] Example 1

[0092] The specific preparation process of the pin structure perovskite solar cell is as follows:

[0093] 1. Prepare a lead-based perovskite precursor solution with a band gap of 1.66 eV: dissolve 0.084 mmol methylamine chloride (6 mol% relative to lead), 0.364 mmol cesium iodide (26 mol% relative to lead), 1.036 mmol formamidine iodide (74 mol% relative to lead), 0.315 mmol lead bromide (22.5 mol% relative to lead), 1.085 mmol lead iodide (77.5 mol% relative to lead), 4.5 mg ethylamine trifluoroacetic acid (2 mol% relative to lead) in a mixed solution of 882 μL N, N-dimethylformamide, 98 μL N-methylpyrrolidone and 20 μL dimethyl sulfoxide, and stir at room temperature for 12 h to make the solution completely uniform;

[0094] 2. Spin-coat a layer of carbazole derivative Me-4PACz ([4-(3,6-Dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid) on a cleaned ITO (indium tin oxide) glass substrate to prepare a hole extraction layer with a thickness of 2 nm;

[0095] 3. Spin-coat 1.4 mg / mL Al2O3 nanoparticle solution on Me-4PACz as a porous insulating contact layer;

[0096] 4. Prepare the perovskite layer by spin coating-antisolvent method in a nitrogen glove box: spin coat the lead-based perovskite precursor solution on the porous insulating contact layer in step 3 at a speed of 5000 r / min for 30 seconds, and anneal on a hot plate at 120° C. for 20 minutes to complete the annealing and crystallization of the perovskite layer;

[0097] 5. Prepare fullerene (C) with a thickness of about 20 nm on the perovskite layer in step 4 by thermal evaporation 60 ) layer as an electron transport layer;

[0098] 6. Prepare a bathocuproin with a thickness of about 5 nm as a hole blocking layer on the fullerene layer in step 5 by thermal evaporation;

[0099] 7. Prepare a silver metal electrode with a thickness of 100 nm on the hole blocking layer in step 6 by thermal evaporation.

[0100] The prepared perovskite solar cells were observed by SEM and their structures were detected by time-of-flight secondary ion mass spectrometry.

[0101] like Figure 1 Shown is a SEM image of the cross section of the perovskite solar cell prepared in Example 1 and the corresponding device structure.

[0102] like Figure 2 As shown, after crystallization is completed, ethylamine trifluoroacetic acid is distributed in the upper and lower interfaces of the perovskite layer and improves the stability of the perovskite solar cell.

[0103] Example 2

[0104] In this embodiment, the content of ethylamine trifluoroacetic acid is 2.3 mg (the molar ratio relative to lead is 1 mol%), and the remaining steps are the same as in Example 1.

[0105] Example 3

[0106] In this embodiment, the content of ethylamine trifluoroacetic acid is 1.2 mg (the molar ratio relative to lead is 0.5 mol%), and the remaining steps are the same as those in Example 1.

[0107] Example 4

[0108] In this embodiment, the content of ethylamine trifluoroacetic acid is 0.6 mg (the molar ratio relative to lead is 0.25 mol%), and the remaining steps are the same as those in Example 1.

[0109] Example 5

[0110] In this embodiment, in step 4, the perovskite layer is prepared in an air glove box with a relative humidity of RH 25% to 30%. The remaining steps are the same as those in embodiment 2.

[0111] Example 6

[0112] In this embodiment, in step 4, the perovskite layer is prepared by a blade coating-vacuum quenching method in a nitrogen glove box:

[0113] (1) The size of the FTO glass (fluorine-doped SnO2 conductive glass) used is 6 cm × 6 cm, and the gap height between the scraper and the porous insulating contact layer is 100-150 μm. The perovskite precursor solution is squeezed into the gap, and then the scraper spreads the perovskite precursor solution on the porous insulating contact layer into a uniform wet film at a speed of 1-1.8 mm / s to obtain a porous insulating contact layer substrate with a spread wet film.

[0114] (2) Rapidly transfer the porous insulating contact layer substrate with the wet film to a sealable chamber for pre-crystallization, evacuate the chamber to maintain the chamber pressure at about 2 Pa, restore the chamber pressure after 3 minutes, place it on a hot plate at 120° C. for annealing for 20 minutes, and complete the annealing and crystallization of the perovskite layer. The remaining steps are the same as those in Example 2.

[0115] The purpose of vacuuming is to evaporate the excess solvent under low pressure, so that the perovskite solute can be quickly saturated, nucleate and crystallize, and complete the transformation of the perovskite film from a wet film to an intermediate phase film.

[0116] Example 7

[0117] In this embodiment, 4.5 mg of ethylamine trifluoroacetic acid is replaced by 2.3 mg of dimethylamine trifluoroacetic acid (the molar ratio relative to lead is 1 mol%), and the remaining steps are the same as in Embodiment 1.

[0118] Example 8

[0119] In this embodiment, a lead-based perovskite precursor solution with a band gap of 1.55 eV is prepared: 0.48 mmol methylamine chloride (30 mol% relative to lead), 1.6 mmol lead iodide (98.2 mol% relative to lead), 0.03 mmol lead bromide (1.8 mol% relative to lead), 0.05 mmol cesium iodide (3 mol% relative to lead), 1.5 mmol formamidine iodide (90 mol% relative to lead), 0.6 mg (0.25 mol% relative to lead) ethylamine trifluoroacetic acid are dissolved in a mixed solution of 800 μL dimethylformamide and 200 μL dimethyl sulfoxide, and stirred evenly. The remaining steps are the same as in Example 1.

[0120] Example 9

[0121] In this embodiment, the content of ethylamine trifluoroacetic acid is 1.3 mg (the molar ratio relative to lead is 0.5 mol%), and the remaining steps are the same as those in Example 8.

[0122] Example 10

[0123] In this embodiment, the content of ethylamine trifluoroacetic acid is 2.5 mg (the molar ratio relative to lead is 1 mol%), and the remaining steps are the same as those in Example 8.

[0124] Comparative Example 1

[0125] In this comparative example, the perovskite precursor solution does not contain an organic salt of trifluoromethyl acid, and the remaining steps are the same as those in Example 1.

[0126] Comparative Example 2

[0127] In this comparative example, the content of ethylamine trifluoroacetic acid in the perovskite precursor solution is 5.8 mg (the molar ratio relative to lead is 2.5 mol%), and the remaining steps are the same as those in comparative example 1.

[0128] Comparative Example 3

[0129] In this comparative example, the content of ethylamine trifluoroacetic acid in the perovskite precursor solution is 11.5 mg (the molar ratio relative to lead is 5 mol%), and the remaining steps are the same as those in comparative example 1.

[0130] Comparative Example 4

[0131] In this comparative example, the content of ethylamine trifluoroacetic acid in the perovskite precursor solution is 23 mg (the molar ratio relative to lead is 10 mol%), and the remaining steps are the same as those in Comparative Example 1.

[0132] Comparative Example 5

[0133] In this comparative example, the perovskite precursor solution does not contain ethylamine trifluoroacetic acid, and the remaining steps are the same as those in Example 5.

[0134] Comparative Example 6

[0135] In this comparative example, the perovskite precursor solution does not contain ethylamine trifluoroacetic acid, and the remaining steps are the same as those in Example 6.

[0136] Comparative Example 7

[0137] In this comparative example, the content of ethylamine trifluoroacetic acid in the perovskite precursor solution is 1.2 mg (the molar ratio relative to lead is 0.5 mol%), and the remaining steps are the same as those in comparative example 5.

[0138] Comparative Example 8

[0139] In this comparative example, the content of ethylamine trifluoroacetic acid in the perovskite precursor solution is 5.8 mg (the molar ratio relative to lead is 2 mol%), and the remaining steps are the same as those in comparative example 5.

[0140] Comparative Example 9

[0141] In this comparative example, the content of ethylamine trifluoroacetic acid in the perovskite precursor solution is 11.5 mg (the molar ratio relative to lead is 5 mol%), and the remaining steps are the same as those in comparative example 5.

[0142] Comparative Example 10

[0143] In this comparative example, the content of ethylamine trifluoroacetic acid in the perovskite precursor solution is 23 mg (the molar ratio relative to lead is 10 mol%), and the remaining steps are the same as those in comparative example 5.

[0144] Comparative Example 11

[0145] In this comparative example, the content of ethylamine trifluoroacetic acid in the perovskite precursor solution is 46 mg (the molar ratio relative to lead is 20 mol%), and the remaining steps are the same as those in comparative example 5.

[0146] Comparative Example 12

[0147] In this comparative example, a layer of ethylamine trifluoroacetic acid was spin-coated between the perovskite layer and the electron transport layer at a rotation speed of 5000 r / min for 30 s as a passivation layer. The concentration of the isopropanol solution of ethylamine trifluoroacetic acid was 1 mg / mL. The remaining steps were consistent with Comparative Example 1.

[0148] Comparative Example 13

[0149] In this comparative example, the concentration of the isopropanol solution of ethylamine trifluoroacetic acid is 2 mg / mL, and the remaining steps are the same as those of comparative example 1.

[0150] Comparative Example 14

[0151] In this comparative example, the concentration of the isopropanol solution of ethylamine trifluoroacetic acid is 3 mg / mL, and the remaining steps are the same as those of comparative example 1.

[0152] Comparative Example 15

[0153] A layer of isopropanol solution of ethylamine trifluoroacetic acid with the same concentration of 1 mg / mL was spin-coated between the perovskite layer and the porous insulating contact layer, and between the perovskite layer and the electron transport layer at a rotation speed of 5000 r / min for 30 s. The remaining steps were consistent with Comparative Example 1.

[0154] Comparative Example 16

[0155] A layer of isopropanol solution of ethylamine trifluoroacetic acid with the same concentration of 2 mg / mL was spin-coated between the perovskite layer and the porous insulating contact layer, and between the perovskite layer and the electron transport layer at a rotation speed of 5000 r / min for 30 s. The remaining steps were consistent with Comparative Example 1.

[0156] Comparative Example 17

[0157] In this comparative example, 5 mol % (molar ratio relative to lead) of dimethylaminoformic acid is added to the perovskite precursor solution, and the remaining steps are the same as those of comparative example 6.

[0158] Comparative Example 18

[0159] In this comparative example, 5 mol% (molar ratio relative to lead) of dimethylaminoformic acid is added to the perovskite precursor solution, and the remaining steps are the same as those of comparative example 1.

[0160] Comparative Example 19

[0161] In this comparative example, the perovskite precursor solution does not contain an organic salt of trifluoromethyl acid, and the remaining steps are the same as those in Example 8.

[0162] Comparative Example 20

[0163] In this comparative example, the final concentration of dimethylaminoformic acid in the perovskite precursor solution is 1 mol% (molar ratio relative to lead), and the remaining steps are the same as those in comparative example 19.

[0164] Test Example 1

[0165] The photovoltaic parameters of the perovskite solar cells prepared in the embodiments and comparative examples were detected. The AM 1.5G spectrum of a standard spectrum solar simulator was used during the test. Before the test, the spectrum intensity was calibrated using a standard silicon solar cell at 100 mW / cm 2 The test was carried out under light intensity.

[0166] Table 1

[0167]

[0168]

[0169]

[0170] The test results are shown in Table 1. Compared with the comparative example, the open circuit voltage and fill factor of the battery in the embodiment are significantly improved, that is, the perovskite containing the organic salt of trifluoromethyl acid shows a higher photoelectric conversion efficiency in a variety of preparation scenarios, indicating that the organic salt of trifluoromethyl acid has universal applicability in improving the photoelectric performance of the battery, and the optimal content is 1 mol% (1.66 eV) or 0.25 mol% (1.55 eV) relative to the lead content in the perovskite precursor solution. The effective area of ​​the battery in Example 6 and Comparative Example 6 is 1.0504 cm 2 The effective area of ​​the battery in other embodiments is 0.0529 cm 2 The device current density-voltage curves of Comparative Example 1 and Optimal Example 2 are as follows: Figure 3 shown.

[0171] The perovskite films obtained in Example 2 and Comparative Example 1 were analyzed. Figure 4It can be seen from the X-ray diffraction spectrum that compared with Comparative Example 1, the lead iodide phase diffraction peak intensity corresponding to about 12.6° in Example 2 is significantly reduced, indicating that the lead iodide content in the example is reduced. The reduction in the ratio of the lead iodide diffraction peak intensity to the perovskite (100) crystal plane diffraction peak intensity corresponding to about 14.1° means that the volatilization or deprotonation of the formamidinium cation is effectively suppressed during the crystallization process, indicating that the perovskite film modified with the organic salt of trifluoromethyl acid has a higher crystal quality. Figure 5 is the X-ray photoelectron spectrum curve of the lead element in the perovskite film. Compared with Comparative Example 1, the 4f peak of lead in Example 1 and Example 2 shifts toward the low binding energy direction, indicating that the carboxyl group of the trifluoroacetate group coordinates with the lead ions in the perovskite, increasing the electron cloud density of the lead, confirming the interaction between the organic salt of trifluoromethyl acid and the perovskite.

[0172] When the perovskite film is prepared by large-area scraping and vacuum quenching, the X-ray diffraction spectra of the perovskite mesophase film after vacuum quenching for different lengths of time in Comparative Example 6 and Example 6 are as follows: Figure 6 and Figure 7 As shown. The specific test method is to vacuum quench the perovskite wet film on the substrate in a closed chamber for 10s, 30s, 1min and 3min respectively, and then take it out immediately for X-ray diffraction test. As the quenching time increases, the peak of lead iodide gradually weakens, and the diffraction peaks of the perovskite (100) and other crystal planes are enhanced. It is worth noting that after vacuum quenching for 3min (i.e., under the preferred experimental conditions), the peak of lead iodide is not measured in Example 6, while there is still residual lead iodide that has not completed the transformation in Comparative Example 6. In addition, the two similar diffraction peaks that appear at about 15° gradually merge into one peak as the vacuum quenching time increases, and the merging speed of Example 6 is faster than that of Comparative Example 1. These two peaks can be considered as the (100) crystal plane diffraction peaks of the bromine-rich phase perovskite and the (100) crystal plane diffraction peaks of the FAPbI3 perovskite. Due to the difference in crystallization dynamics and grain size, the bromine-rich phase crystallizes and precipitates first during the crystallization process, and then merges with the FA phase to achieve homogenized growth of grains. Figure 6 and Figure 7 It is shown that the organic salt of trifluoromethyl acid can promote the combined growth of different component phases of wide-bandgap perovskite during vacuum quenching, improve the phase uniformity of the film, and positively improve the pre-crystallization uniformity of large-area preparation.

[0173] Furthermore, the performance of the complete perovskite device with and without the organic salt additive of trifluoromethyl acid was tested. Figure 8The curve of the electroluminescent quantum efficiency (ELQE) of the device changes with the injection current density. The ELQE of the perovskite solar cell modified with the organic salt of trifluoromethyl acid is significantly higher than that of the device in Comparative Example 1, indicating that the device prepared in Example 2 has higher perovskite film quality and lower opening voltage loss, which is consistent with the results in Table 1. The maximum power point tracking stability test results of the device are shown in Fig. 9 The test light intensity is 100mW / cm2 calibrated under AM1.5G 2 , the test temperature is 35°C, and an efficiency point is recorded every 5 minutes. Under the same test conditions, the photoelectric conversion efficiency of the battery in Example 1 is reduced to 80% of the initial efficiency after 400 hours, while the battery in Example 2 still maintains an initial efficiency higher than 90% during the test process of nearly 500 hours, which fully demonstrates the effect of the organic salt of trifluoromethyl acid on improving the stability of the device.

[0174] It can be seen from Example 1 and Comparative Examples 1 to 4 that when preparing the perovskite layer in nitrogen, a too high content of ethylamine trifluoroacetic acid does not improve the performance of the battery and causes the perovskite precursor solution to crystallize too quickly and uncontrollably during the spin coating process.

[0175] It can be seen from Example 5, Comparative Example 5, and Comparative Examples 7 to 11 that when the perovskite layer is prepared in air, the battery performance decreases after the content of ethylamine trifluoroacetic acid reaches 5 mol%.

[0176] It can be seen from Comparative Examples 1 and 12 to 16 that spin coating the organic salt of trifluoromethyl acid as a passivation layer has no significant improvement on the battery performance.

[0177] Depend on Fig.10 , Fig.11 and Fig.12It can be seen that due to the difference in crystallization dynamics and grain size, the bromine-rich phase crystallizes first during the crystallization process, and then merges with the pure iodine phase to achieve uniform growth of the grains. The most representative (100) crystal plane diffraction peak of perovskite is selected, and the split peak of about 2θ=14.2° is used for comparison and explanation. For cesium-rich bromine-rich wide band gap perovskite, the low angle is the (100) crystal plane diffraction peak of FAPbI3 perovskite with a larger grain size, and the high angle is the (100) crystal plane diffraction peak of bromine-rich phase perovskite. The two similar diffraction peaks gradually merge into one peak as the vacuum quenching time increases. The merging speed of the two different component perovskite phases in Example 6 is faster than that of Comparative Example 6 (curve at 1min), but there is no obvious difference between Comparative Example 6 and Comparative Example 17, indicating that the addition of dimethylaminoformic acid in Comparative Example 17 has no phase homogenization effect. Similarly, in Comparative Example 17, the perovskite layer was prepared by blade coating-vacuum quenching in a nitrogen glove box, and in Comparative Example 18, the perovskite layer was prepared by spin coating-antisolvent method in a nitrogen glove box, but the addition of dimethylaminoformic acid was still not as good as the addition of trifluoromethyl acid organic salt in Example 1. In addition, there was no significant difference between Comparative Example 19 and Comparative Example 20, and the above conclusion was also confirmed in the perovskite with a band gap of 1.55 eV.

[0178] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A perovskite precursor solution, characterized in that: The perovskite precursor solution contains a perovskite precursor solute, a perovskite precursor solvent and an additive; The perovskite precursor solute contains lead halide and at least one of tin halide, formamidine halide, methylamine halide, cesium halide, dimethylamine halide and guanidine halide; The perovskite precursor solvent contains at least one of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol, valerolactone and acetonitrile; The additive contains an organic salt of trifluoromethyl acid.

2. The perovskite precursor solution according to claim 1, characterized in that: The organic salt of the trifluoromethyl acid contains at least one of methylamine ion, ethylamine ion, dimethylamine ion and ethylenediamine ion, and the trifluoromethyl acid includes one of trifluoroacetic acid, trifluoropropionic acid, trifluorobutyric acid and trifluoromethylbenzoic acid.

3. The perovskite precursor solution according to claim 1, characterized in that The molar ratio of the organic salt of trifluoromethyl acid to lead in the perovskite precursor solute is 0.01 to 5 mol%.

4. The method for preparing the perovskite precursor solution according to any one of claims 1 to 3, characterized in that: The perovskite precursor solute, the perovskite precursor solvent and the additive are uniformly mixed to obtain the perovskite precursor solution.

5. Use of the perovskite precursor solution according to any one of claims 1 to 3 in the preparation of perovskite solar cells, perovskite light-emitting diodes, perovskite lasers, perovskite photodetectors and / or optical chips.

6. A method for preparing a perovskite solar cell, characterized in that: The following steps are involved: S1: Preparation of hole extraction layer on conductive glass; S2: preparing a porous insulating contact layer on the hole extraction layer in step S1; S3: depositing a perovskite layer on the porous insulating contact layer obtained in step S2 using the perovskite precursor solution according to any one of claims 1 to 3; S4: preparing an electron transport layer on the perovskite layer in step S3; S5: preparing a hole blocking layer on the electron transport layer in step S4; S6: preparing a back electrode layer on the hole blocking layer in step S5.

7. The preparation method according to claim 6, characterized in that: In step S3, the perovskite layer is deposited in nitrogen and / or air.

8. The preparation method according to claim 6, characterized in that: In step S3, the method of depositing the perovskite layer is at least one of spin coating, doctor blading, slit coating, inkjet printing and screen printing.

9. The preparation method according to claim 6, characterized in that: In step S4, an electron transport layer is prepared using an n-type semiconductor material.

10. The perovskite solar cell prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Perovskite precursor solution, preparation method thereof and perovskite solar cell

    CN114141953A

  • High-stability perovskite solar cell based on co-modification of trifluoroacetic acid organic salt and inorganic salt

    CN115768148A

  • Perovskite solar cell containing double trifluoroacetate modification layers and preparation method thereof

    CN115915795A

  • Method for optimizing perovskite thin film, obtained perovskite thin film and application

    CN117015282A

  • Cesium-formamidine-based lead-iodine alloy perovskite active layer and preparation method and application thereof

    CN117794334A

Cited By

  • Perovskite precursor solution additive, solution, solar cell and preparation method

    CN120711986A

  • Perovskite precursor material for photoelectric conversion and preparation method thereof

    CN121450114A